Research Progress and Prospect of Ecological Flow Based on Indicator Species - ZHANG Yue; ZHANG Jie; LIU Xingchen; WANG Kai; JI Yong (Renmin Zhujiang)
The ecological flow of rivers and lakes maintains the self-purification diffusion abilityrequired by the river, protects the integrity of the structure and function of river and lakeecosystems. Therefore, it has become a research hotspot in the field of water resources. Based onthe research progress on the ecological flow, this paper summarizes the application of ecologicalindicator species and hydrological factors in ecological flow research, clarifies the effect ofspecies behavior on the aquatic environment under the change of hydrological factors, and proposesthe remaining problems and prospects of current research on ecological flow, which can providescientific guidance for the future research and application of ecological flow based on indicatorspecies.